2022
DOI: 10.3390/mi13112006
|View full text |Cite
|
Sign up to set email alerts
|

A Monocular-Visual SLAM System with Semantic and Optical-Flow Fusion for Indoor Dynamic Environments

Abstract: A static environment is a prerequisite for the stable operation of most visual SLAM systems, which limits the practical use of most existing systems. The robustness and accuracy of visual SLAM systems in dynamic environments still face many complex challenges. Only relying on semantic information or geometric methods cannot filter out dynamic feature points well. Considering the problem of dynamic objects easily interfering with the localization accuracy of SLAM systems, this paper proposes a new monocular SLA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 51 publications
(53 reference statements)
0
3
0
Order By: Relevance
“…It also introduces an inertial sensor to minimize the scale variance of monocular-vision-only SLAM. Further improvements are also proposed with sensor adaptability, dynamic environment, online calibration, and pose-graph reuse [ 32 , 33 , 34 , 35 , 36 ].…”
Section: Related Workmentioning
confidence: 99%
“…It also introduces an inertial sensor to minimize the scale variance of monocular-vision-only SLAM. Further improvements are also proposed with sensor adaptability, dynamic environment, online calibration, and pose-graph reuse [ 32 , 33 , 34 , 35 , 36 ].…”
Section: Related Workmentioning
confidence: 99%
“…The final experimental data are shown in Table 1. Analyzing Table 1, it is found that without preprocessing by the map partition algorithm, the average computing time required by the JPS algorithm for tasks (1,9) and (5,3) is 1.8825s and 2.5562s, respectively. However, after preprocessing by the map partition algorithm, the average calculation time of JPS in the same task was shortened to 1.4762s and 2.0639s.…”
Section: Indoor Partition Preprocessing Algorithm Experimentsmentioning
confidence: 99%
“…Indoor mobile robots [1] represent a significant research direction in the field of robotics technology. The pace of research and application has accelerated in recent years, showcasing a broad range of potential applications in indoor settings such as homes, offices, medical and educational institutions, among others.…”
Section: Introductionmentioning
confidence: 99%